Aerospace and military [Technology 2000 analysis and forecast]. - Scott, P. (IEEE spectrum)
If aerospace has not met the best and brightest predictions of a half-century ago, the years ahead still promise plenty of action. As the millennium turns, China and perhaps France will soon join the United States and Russia in being able to put men and women into space aboard their own home-built transports. And the demand for satellite launch services is booming, as last year saw the first commercial flight of the Ariane 5 rocket and the first commercial liftoff from Sea Launch, the innovative ocean-based launch platform. NASA, meanwhile, is still smarting from the back-to-back losses of two Mars probes and the temporary shutdown of its orbiting Hubble Space Telescope. On the military front, the US Air Force continues to push for the F-22 fighter aircraft, even as some in Congress would declare it dead in favor of the Joint Strike Fighter. Advanced submarines are on the drawing boards of several countries, including the United States. Plans for these underwater behemoths, like their highly maneuverable airborne brethren, call for ever-increasing amounts of automation and electronics. Civil aviation, after taking much flak in 1999 for overcrowded skies and Y2K impacts on air travel, is pushing confidently into the next century. Global positioning systems (GPS) are inspiring advances in navigational equipment, and replacement systems for outmoded air traffic control set-ups draw ever closer to widescale deployment. A big obstacle remains, however, to fulfilling these goals in the next century. It is the same one as has delayed putting a person on Mars or building an orbiting space station-the price tag